Energetics of floor gymnastics: aerobic and anaerobic share in male and female sub-elite gymnasts - Kaufmann, S.; Ziegler, M.; Werner, J.; Noe, C.; Latzel, R.; Witzany, S.; Beneke, R.; Hoos, O. (Sports Medicine - Open, 2022)
Key Points